Life's edge : the search for what it means to be alive - Zimmer, Carl, 1966- (New York, NY ; Dutton, an imprint of Penguin Random House LLC, 2021)
"We all assume we know what life is, but the more scientists learn about the living world-from protocells to brains, from zygotes to pandemic viruses-the harder they find it is to locate life's edge"--
What is life? The power seems obvious until you try to seriously answer it. Zimmer journeys through experiments that have attempted to recreate life; shows how coronaviruses have altered the course of history; and even tries his own had at evolving life in a test tube... with unnerving results. -- adapted from jacket
Introduction: The borderland -- The quickening. The way the spirit comes to the bones ; Death is resisted -- The hallmarks. Dinner ; Decisive matter ; Preserving constant the conditions of life ; Copy/Paste ; Darwin's lung -- A series of dark questions. This astonishing multiplication ; Irritations ; The sect ; This mud was actually alive ; A play of water ; Scripts -- Return to the borderland. Half life ; Data needed for a blueprint ; No obvious bushes ; Four blue droplets.
Includes bibliographical references (pages 293-334) and index.
108761
Keywords: Life sciences; Life (Biology); Instructional and educational works; Creative nonfiction